2022
DOI: 10.1021/acs.langmuir.2c01735
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae as Soft Permeable Particles

Abstract: The colloidal stability of non-motile algal cells in water drives their distribution in space. An accurate description of the interfacial properties of microalgae is therefore critical to understand how microalgae concentrations can change in their biotope or during harvesting processes. Here, we probe the surface charges of three unicellular algae�Chlorella vulgaris, Nannochloropsis oculata, and Tetraselmis suecica�through their electrophoretic mobility. Ohshima's soft particle theory describes the electrokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…Accordingly, differences between bVLP and eVLP could not be detected, and similar adsorption behavior can be expected during chromatographic purification. In addition, the values for both parameters are comparable with values reported for other biological particles in the literature. Sonohara et al and de Kerchove and Elimelech reported a hydrodynamic penetration length of approximately 0.7 nm and a number density of charges ZN of about −145 mmol l –1 for E. coli cells.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Accordingly, differences between bVLP and eVLP could not be detected, and similar adsorption behavior can be expected during chromatographic purification. In addition, the values for both parameters are comparable with values reported for other biological particles in the literature. Sonohara et al and de Kerchove and Elimelech reported a hydrodynamic penetration length of approximately 0.7 nm and a number density of charges ZN of about −145 mmol l –1 for E. coli cells.…”
Section: Resultssupporting
confidence: 84%
“…A well-known and commonly used model to describe the electrokinetic phenomena for monodispersed, nonconducting particles is based on the Helmholtz–Smoluchowski equation μ = ζ ε 0 ε r η …”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations